DEVELOPMENT OF LOGICAL COMPETENCES OF FUTURE PRIMARY SCHOOL TEACHERSDEVELOPMENT OF ELECTRONIC METHODOLOGICAL SUPPORT (American Journal of Pedagogical and Educational Research, 2025)
This article is based on a creative approachdevelopment of logical competencies of future primary school teachersImproving electronic methodological supportThe methodology and, as a consequence, effective methods for developing logical competencies of future primary school teachers are described.